Gambaran Proteinuria dan Glukosuria pada Ibu Hamil Berdasarkan Usia dan Trimester Kehamilan di Puskesmas Teladan Medan - Indrayani Kristina Simanjuntak; Sartini Sartini; Rahmiati Rahmiati; Rahma Sari Siregar (Universitas Medan Area, 2026)
Proteinuria and glucosuria are important indicators for monitoring maternal health during pregnancy because they are associated with the risk of preeclampsia and gestational diabetes mellitus. This study aimed to describe the occurrence of proteinuria and glucosuria among pregnant women based on maternal age and gestational trimester at Teladan Primary Health Center, Medan, in 2023. A descriptive quantitative study with an observational approach was conducted involving 30 pregnant women selected through purposive sampling. Urine protein was examined using the 6% acetic acid method, while urine glucose was assessed using the Benedict reduction method. The results showed that most participants were aged 21–30 years (70.0%) and were in the second trimester of pregnancy (46.7%). Urine protein examination revealed negative results in 25 participants (83.3%), proteinuria of +1 in 4 participants (13.3%), and proteinuria of +2 in 1 participant (3.3%). Urine glucose examination showed negative results in 29 participants (96.7%) and positive results in 1 participant (3.3%). Proteinuria was observed among pregnant women with elevated blood pressure and a history of hypertension, whereas glucosuria was identified in a participant with a history of diabetes mellitus. In conclusion, most pregnant women had normal urine protein and glucose levels; however, routine urine screening remains essential for the early detection of pregnancy-related complications.